Expert System for Diagnosing Pests on Oil Palm Seed Plants Using the Certainty Factor Method - Fikri, Muhammad Ihsanul; Nasution, Yusuf Ramadhan (Newinera Publisher, 2024)
Indonesia is one of the largest countries producing palm oil. The problems that often arise in oil palm seedlings are pest attacks. Oil palm seedlings diagnosed with pest attacks can be characterized by existing symptoms. Based on the phenomena that occurred, researchers created a system for diagnosing pests in oil palm seed plants, so that they could diagnose quickly and find solutions to pest problems in oil palm seed plants. This research uses a development method called waterfall. The design of this research is to plan an Expert System for Diagnosing Pests on Oil Palm Seed Plants Using the Certainty Factor Method. Based on the tests that have been carried out, the results are that the community or farmers on oil palm plantations can easily diagnose pests on oil palm seed plants in real time as long as they are connected to the internet to help diagnose pests on oil palm seed plants. Testing of the expert system showed a high level of accuracy in diagnosing pests on oil palm seedlings. The level of suitability accuracy reached more than 90%. With this expert system, oil palm plantation management can be improved significantly. Early detection of pest attacks will reduce the losses incurred and allow more effective preventive measures to be taken.